Laparoscopically assisted vaginal hysterectomy. Preliminary report on 12 cases. - Seminario, Jaime (2015)
The is a critical study on indications, complications and results of vaginal hysterectomy assisted by laparascopy, technique that is being introduced in our country, resulting in small wounds and  decrease of both hospitalizations days and postoperative pain.